Diet and Women: A Complex Relationship That We Need to Know Better [Response to Letter] - AlQuaiz A; Kazi A (Dove Medical Press, 2023)
AlJohara AlQuaiz,1,2 Ambreen Kazi1 1Princess Nora Bent Abdullah Chair for Women’s Health Research, King Saud University Medical City, Riyadh, Saudi Arabia; 2Department of Family & Community Medicine, King Saud University Medical City, Riyadh, Saudi ArabiaCorrespondence: Ambreen Kazi, Princess Nora Bent Abdullah Research Chair for Women’s Health Research, King Saud University Medical City, PO Box 231831, Riyadh, 11321, Saudi Arabia, Tel +966 1 4692714, Fax +966 1 4691127, Email akamran@ksu.edu.sa